2021
DOI: 10.1021/acs.analchem.1c02896
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Identification Using Infrared Ion Spectroscopy─Novel Biomarkers for Pyridoxine-Dependent Epilepsy

Abstract: Untargeted liquid chromatography−mass spectrometry (LC−MS)-based metabolomics strategies are being increasingly applied in metabolite screening for a wide variety of medical conditions. The long-standing "grand challenge" in the utilization of this approach is metabolite identificationconfidently determining the chemical structures of m/z-detected unknowns.Here, we use a novel workflow based on the detection of molecular features of interest by high-throughput untargeted LC−MS analysis of patient body fluids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 42 publications
3
30
1
Order By: Relevance
“…A similar fragmentation pattern was observed for the P6C analogs we previously annotated 9 , 10 , namely the neutral loss of C 3 H 6 O for feature A and B and C 2 H 4 O 2 for feature C. We, therefore, hypothesized a similar structure and connectivity of these fragments to the P5C-core leading to the proposed structures of 2-OPC ( 4 ) and CPC ( 5 ) (Fig. 1d ).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…A similar fragmentation pattern was observed for the P6C analogs we previously annotated 9 , 10 , namely the neutral loss of C 3 H 6 O for feature A and B and C 2 H 4 O 2 for feature C. We, therefore, hypothesized a similar structure and connectivity of these fragments to the P5C-core leading to the proposed structures of 2-OPC ( 4 ) and CPC ( 5 ) (Fig. 1d ).…”
Section: Resultssupporting
confidence: 80%
“…In contrast, the calculated frequency belonging to the NH 2 -vibration does not match well with the experimentally obtained spectra for features A and B. This discrepancy can be attributed to the anharmonic behavior of the NH bending mode, resulting in a redshift in spectra predicted within the harmonic approximation 14 , 15 , as was noted before for the corresponding P6C biomarker 9 . Overall the spectral region between 1200 and 1500 cm −1 is adequately predicted by the computed spectra.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…Thus, far, only a small number of studies have used metabolomics to investigate epileptogenesis. 21 - 24 Heischmann et al 22 explored the hippocampal and plasma metabolome in the rat kainic acid model of mesial temporal lobe epilepsy (MTLE) at different time points during epileptogenesis. The authors found that disease development was associated with perturbations in vitamin D3 metabolism, which is important for mitochondrial function, red-ox processes, and immune modulation.…”
Section: Introductionmentioning
confidence: 99%